Mechanical Properties of Sustainable Concrete Reinforced with Micro Steel Fibers - Alkhafaji, Sura F.; Abduljabbar, Rawya A.; Abdulhussein, Samer S.; Hussain, Hussain D.; Khalid, Hajer R. (Engineering, Technology & Applied Science Research, 2025)
One of the most important solutions for producing sustainable concrete is the utilization of old concrete as coarse aggregate. This study evaluates the full replacement of coarse aggregate with recycled aggregate and the impact of micro steel fibers on the mechanical properties of concrete using a combination of non-destructive and destructive tests. The deployed methodology includes five concrete mixes incorporating 0%, 0.4%, 0.6%, 0.8%, and 1% micro steel fibers by volume to produce sustainable concrete reinforced with fibers. The non-destructive tests examined density, Ultrasonic Pulse Velocity (UPV), and dynamic modulus of elasticity, while the destructive tests examined compressive strength, static modulus of elasticity, splitting tensile strength, and flexural strength. The results demonstrate the possibility of adopting zero-cost coarse aggregate produced from old concrete as a sustainable aggregate. Furthermore, the mechanical properties of concrete are enhanced by adding micro steel fibers. The optimal performance was observed at 0.8 % fibers with maximum improvements of 15 % in compressive strength, 39.2 % in splitting tensile strength, and approximately 85 % in flexural strength at 28 % days. The UPV and density values exhibited strong correlations with the compressive strength. Finally, the findings of this study support that the recycled aggregate and micro steel fibers can be used to produce sustainable concrete for modern constructions.